KINERJA PEGAWAI DALAM PElAYANAN KTP DI KANTOR CAMAT SINDUE KABUPATEN DONGGALA - Hilman, Hilman (Katalogis, 2015)
This study aims to determine how the performance of employees in the service of e-ID card in Sindue Donggala District Office. This research using qualitative methods. As for the informants in this study were employees and the community Sindue District of Donggala, as for the data used in this study are primary data and secondary data through observation and interviews with employees of Head Office Sindue with the District Public Sindue, in this study research Performance Concept of Agus Dwiyanto consists of five indicators, namely: Productivity, Quality of Service, Responsiveness, Responsibility, and Accountability. The performance of employees in the service of ID card in Sindue Donggala District Office based on results of the study found that the performance of employees in the service of ID in the District Office Sindue still sluggish and less effective. The results also revealed that the service performance of employees is not maximized it is closely related to the responsibility or accountability of employees and service quality districts which include the ability responsiveness in providing services. While productivity and responsibility was also still relatively low it is closely related to the quality of employee performance is a reflection of poor employee performance to the public.